Pengaruh Kemasan, Harga dan Kualitas Produk Terhadap Minat Minat Beli Ulang Konsumen Mixue Ahmad Yani Metro - Nurul Kolifatun; Ardiansyah Japlani; Nina Lelawati (Universitas Muhammadiyah Metro, 2026)
The purpose of this study was to analyze the effect of packaging, price, and product quality on consumer repurchase interest at Mixue Ahmad Yani Metro. With respondents totaling 68 consumers.This type of research uses the causal association method and the descriptive method using a quantitative approach. This study uses sampling techniques such as non-probability sampling, purposive sampling, and accidental sampling. Data collection in this study involves observation, interviews, and questionnaires.The results of this study indicate that: (1) Packaging has a significant effect on the Repurchase Interest variable with a tcount value of 2.477> t table 1.997. (2) Price has a significant effect on the Repurchase Interest variable with a tcount value of 4.599> t table 1.997. (3) Product quality has a significant effect on repurchase interest, with a tcount value of 1.284 < ttable 0.1997. (4) Packaging, Price and Product Quality have a positive and significant effect together on Repurchase Interest with an Fcount value of 66.987, which is positive and > from the Ftable value of 2.75.